Métodos númericos para resolución de estrategias de carrera basadas en pacing o ritmo (2020)
Bycicle is a human traction vehicle thus its optimal dynamic depends on cyclist factors such as physical performance and muscular capacity. For this reason, in clyclism several strategies has been developed in order to complete a track in the minimum posible time, considering different variables as incidence of wind, elevation profile and physiological parameters of the athlete. Actually, strategies of drag coefficient reduction, bycicle change and optimal power distribution also known as Pacing, which is the subject matter of this research. Two optimal control methods are introduced to analyze the pacing strategy behavior on constant and variable elevation profiles dnd by this way, analyze power, velocity and anaerobic energy reserve delivery. Consequently, the first method based on Matlab uses an the steepest descent resolution while the second one is developed on Pyomo which is a programming language rooted on Python. It is found several advantajes and disadvantajes between this two methods of resolution. While Pyomo is powerful in definition of minimum time problem statements Matlab can reduced optimal time by 1.96% but has to spent so much more computational resources.